Paradigma Jemaat Terhadap Pendeta Penyandang Disabilitas: Studi Teologi Disabilitas dalam Konteks Jemaat GKE Selat Kapuas - Retni Mulyani; Alexandra Binti; Sri Winda Yanti; Elvi Sumbu (Jurnal Teologi Pambelum, 2023)
The congregation's paradigm towards persons with disabilities in the context of the Kapuas Strait GKE Congregation is seen from the medical model and social model. The medical model is also said to be an individual model which places people with disabilities at normal standards that have been determined by non-disabled people. The medical model is a paradigm that was criticized by Michael Oliver who then offered the social model as a new paradigm in viewing socially disabled people in a more human way. It is also supported by the idea of Thomas Reynolds that the medical model is not something that is forbidden but is equipped with a social model because after all social models produce physiological conditions that cannot be eliminated. Through the results of the research, it was found that congregations can accept pastors with disabilities and they place their pastors in an equal place and provide space that allows pastors with disabilities to make a contribution. However, on the other hand it is also found that the understanding of the congregation is on two sides between the medical model and the social model. This means that medical understanding is still embedded in their memory